Hydraulic and volume change characteristics of compacted clay liner blended with exfoliated vermiculite. (23rd March 2020) - Baldev, Dharmil; Kumar, Apurv; Chauhan, Pavan; Muthukumar, M.; Shukla, Sanjay Kumar
Clays are used for the construction of waste containment barriers, because of its low hydraulic conductivity. Due to the difficulty in obtaining the natural clay satisfying the essential requirement as a liner material; commercially available bentonites are being used for the construction of clay liners. Bentonite undergoes large volume changes upon saturation. Various physical and chemical stabilisation techniques are in practice to stabilise the bentonite. Previous studies reported that contaminants with high concentrations attack clay minerals leading to increase in their permeability. Exfoliated vermiculite, finds several applications in construction industry, also found to be good absorbent material. Hence, this study has been carried out to find the optimal percentage of vermiculite that can be added to the bentonite so that it satisfies the essential requirements of clay liners and absorb the heavy metals from contaminants. Several index properties and engineering properties tests on bentonite-vermiculite mixtures were performed. From the studies, it was found that 30% of vermiculite can be added to bentonite, so that the essential requirements of liner can be maintained.